The perfect gentleman : the representation of men in the English gothic novel, 1762-1820 - Behr, K (1993)
This thesis examines the representation of male character stereotypes as manifestations of a formula in late eighteenth-century popular fiction. In order to establish the presence of the formula, I have inspected a wide spectrum of both familiar and lesser-known works. Much recent criticism has focused on the passive figure of the heroine as one expression of female anxiety within the texts. In contrast, this thesis draws attention to the critically unseen, active figures surrounding her threatened perfection, by establishing, first, a common representation or role within the formula for each stock character and, second, the source and possible effect of these stereotypes. In Chapters One and Two, the parameters for this approach are set up and the influences of other genres on characterization in the Gothic romance are considered. Chapter Three establishes the eighteenth-century ideal of masculinity through an investigation of contemporary conduct literature. These standards are then applied to stock male figures in succeeding chapters. Chapters Four, Five and Six consider the primary male figures of hero, father and villain, revealing that the ideal of masculine perfection affects all these stereotypes. The nature of heroism is questioned in the person of the hero; the father - an exemplum of gentlemanly perfection - is made absent within the text; and the villain reinforces this ideal by perverting it. Chapter Seven considers the representation of the victim figure and the way in which the stereotype of masculinity indirectly victimizes male figures. In Chapter Eight, three groups of secondary male characters are considered and their relationship to the primary male characters examined. This analysis of male stereotypes has, therefore, provided one approach to an understanding of Gothic conventions.